Faktor Kesulitan Guru Dalam Proses Belajar Mengajar Di Ditinjau Dari Pengunaan Kurikulum, Struktur Materi, Sarana Dan Prasarana, Dan Alokasi Waktu - Kadariah Kadariah; Kusmaladewi Kusmaladewi; Hasmiah Hasmiah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2020)
This study aims to find a picture of the difficulties experienced by teachers in the implementation of learning activities and the steps taken to overcome the difficulties encountered in learning. The research approach uses descriptive qualitative research to explain the phenomena of difficulties experienced by teachers in carrying out learning activities and steps taken to overcome difficulties encountered in learning. The data collection techniques used in this study were open questionnaires as primary data sources and observations. Data analysis uses descriptive statistics, to obtain a picture of the difficulty factors and the steps in implementing learning. The results showed that the implementation of the curriculum for learning activities and in formulating basic competencies were still the difficulties of subject teachers. The structure of the material in the learning curriculum is still an obstacle for the teacher because the material is not in accordance with the level of student ability. The availability of facilities and infrastructure as well as the allocation of time still need to be a major concern in improving the quality of learning.